RD&D Literature Review for Development of a Digital Platform for the Learning Supervision Evaluation Model (MESp) - Eny Winaryati; Muhamad Munsarif; Mardiana Mardiana; Suwahono Suwahono (Pendidikan Kimia Unimus, 2021)
This article discuss about the RD&D stages that will be used to develop the MESp digital platform. This RD&D stage is done in stages and cyclically. Each phase is evaluated, with the hope that a valid, practical and effective product will be produced, and has been tested. The development of the MESp digital platform uses the RD&D method, using the literature review method. The RD&D phases consist of: Research (Analysis, Define), Development (Design, Demonstration, Development), Diffusion (Delivery, Diffusion, Adoption). Each phase is equipped with sub-activities that must be done. Each phase evaluates PAI (Purphose, Activities, Interim Product). Users are allowed to move to the next phase, when an evaluation has been produced that can answer: the achievement of its objectives, the activities that have been done, and the temporary products produced. Users are given the freedom to add sub-activities from each phase, if that necessary and for a clear reason.